Nutritional Support for Patients with Pancreatic Cancer - Min Kyu Jung (The Korean Journal of Gastroenterology, 2019)
Pancreatic cancer is the ninth common malignancy in South Korea. It has a dismal prognosis with a 5-year overall survival rate of less than 10%, and pancreatic cancer is associated with cancer cachexia, which is defined as the loss of muscle mass that is not reversible by conventional nutritional support. Cachexia is noted in over 85% of all pancreatic cancer patients and it is strongly related with the disease’s mortality. Nearly 30% of pancreatic cancer deaths are due to cachexia rather than being due to the tumor burden. Therefore, it is crucial to discover the mechanisms behind the development of muscle wasting in pancreatic cancer patients and find novel therapeutics for targeting cachexia. This review deals with the current understanding about the development of cachexia and nutritional support in those patients suffering with pancreatic cancer.